Progressive Muscle Relaxation and Warm Foot Bath Therapy for Type 2 Diabetes Patients - Ismansyah Ismansyah; Arif Supriyanto; Frana Andrianur; Rini Ernawati (MEDICA (International Medical Scientific Journal), 2026)
Hospitalised patients with type 2 diabetes mellitus (T2DM) are often exposed to situational anxiety that activates the hypothalamic–pituitary–adrenal (HPA) axis, increases cortisol levels, and contributes to poor glycaemic control; therefore, complementary non-pharmacological nursing interventions that reduce stress may enhance standard treatment outcomes. This study aimed to compare the effects of progressive muscle relaxation (PMR) and warm water foot bath therapy (WWFB) on random blood glucose (RBG) levels among hospitalised patients with T2DM receiving standard care. A parallel three-arm randomised controlled trial was conducted in three inpatient wards of Pupuk Kaltim Hospital, Bontang, between August and September 2025, involving 48 patients with admission RBG ≥ 200 mg/dL who were randomly assigned to PMR, WWFB, or control groups in equal proportions using computer-generated randomisation with allocation concealment. The interventions were administered for 15–20 minutes once daily over three consecutive days, and outcome assessors were blinded to group allocation. Data were analysed using paired t-tests, one-way ANOVA with Tukey HSD post-hoc tests, and effect size measures. The results showed significant reductions in RBG within all groups, with greater decreases observed in the PMR and WWFB groups compared to the control group. Furthermore, there was a statistically significant difference in post-intervention RBG between groups, where both PMR and WWFB demonstrated superior effects compared to standard care, while no significant difference was found between the two intervention groups. In conclusion, both progressive muscle relaxation and warm water foot bath therapy are effective complementary nursing interventions for improving glycaemic control in hospitalised patients with T2DM and may be integrated into routine clinical practice to support diabetes management.